Assessing Population Genetic Status for Designing Plant Translocations - Van Rossum, Fabienne; Le Pajolec, Sarah; Raspé, Olivier; Godé, Cécile (Frontiers in Conservation Science, 2022)
Assisted gene flow interventions such as plant translocations are valuable complementary techniques to habitat restoration. Bringing new genetic variants can contribute to increasing genetic diversity and evolutionary resilience, counteract inbreeding depression and improve plant fitness through heterosis. Large, highly genetically variable populations are usually recommended as sources for translocation. Unfortunately, many critically endangered species only occur as small populations, which are expected to show low genetic variation, high inbreeding level, paucity of compatible mates in self-incompatible species, and increased genetic divergence. Therefore, assessment of population genetic status is required for an appropriate choice of the source populations. In this paper, we exemplify the different analyses relevant for genetic evaluation of populations combining both molecular (plastid and nuclear) markers and fitness-related quantitative traits. We assessed the genetic status of the adult generation and their seed progeny (the potential translocation founders) of small populations of Campanula glomerata (Campanulaceae), a self-incompatible insect-pollinated herbaceous species critically endangered in Belgium. Only a few small populations remain, so that the species has been part of a restoration project of calcareous grasslands implementing plant translocations. In particular, we estimated genetic diversity, inbreeding levels, genetic structure in adults and their seed progeny, recent bottlenecks, clonal extent in adults, contemporary gene flow, effective population size (Ne), and parentage, sibship and seed progeny fitness variation. Small populations of C. glomerata presented high genetic diversity, and extensive contemporary pollen flow within populations, with multiple parentage among seed progenies, and so could be good seed source candidates for translocations. As populations are differentiated from each other, mixing the sources will not only optimize the number of variants and of compatible mates in translocated populations, but also representativeness of species regional genetic diversity. Genetic diversity is no immediate threat to population persistence, but small Ne, restricted among-population gene flow, and evidence of processes leading to genetic erosion, inbreeding and inbreeding depression in the seed progeny require management measures to counteract these trends and stochastic vulnerability. Habitat restoration facilitating recruitment, flowering and pollination, reconnecting populations by biological corridors or stepping stones, and creating new populations through translocations in protected areas are particularly recommended.